A ball milling calcination preparation method of a carbon nanotube and glucose composite coated sodium iron pyrophosphate sulfate positive electrode material

CN122897382APending Publication Date: 2026-10-13BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611168488.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

葡萄糖原位热解虽分散均匀,但残碳率低、石墨化程度差,难以形成高效导电网络;导电炭黑虽电子传输快,但疏水性强、易团聚,与活性材料界面接触差,且额外增加电极制备工序

Benefits of technology

[0014]本发明公布了一种碳纳米管和葡萄糖复合包覆硫酸焦磷酸铁钠正极材料的球磨煅烧制备方法。该方法基于机械化学辅助固相合成策略,首次在硫酸焦磷酸盐体系中实现碳纳米管与葡萄糖双碳源的同步引入与协同包覆,成功构筑了Na2Fe2P2O7SO4/CNT-Glu复合正极材料。该复合聚阴离子骨架巧妙融合了硫酸盐的高电压特性与焦磷酸盐的高热力学稳定性:硫酸根凭借强电负性诱导效应有效抬升Fe3+/Fe2+氧化还原电位,而焦磷酸根以稳固的共价键网络抑制晶格氧流失,两者协同突破了单一硫酸盐煅烧窗口窄(<400 ℃)与单一焦磷酸盐的固有瓶颈。工艺层面,高能球磨实现了多组分离子级均匀分散;同时,葡萄糖在煅烧过程中原位热解为高活性无定形碳,与外加碳纳米管交织形成“线-点”结合的三维混联导电骨架——碳纳米管作为长程电子输运主干道,无定形碳作为界面亲和桥梁,二者协同显著降低电极极化阻抗,改善活性材料与电解液的浸润性。实验数据表明,利用本发明方法制备的Na2Fe2P2O7SO4-CNT-2-Glu-3复合材料在0.05 C倍率下初始放电比容量达114.09mAh/g,0.2 C倍率下的可逆放电比容量为95.37 mAh/g,2 C倍率下可逆放电比容量为83.40mAh/g且循环400圈容量保持率达91.56%,综合性能显著优于单一碳源包覆体系。本发明为兼具高电压、长寿命、低成本优势的钠离子电池正极材料规模化制备提供了切实可行的技术路线。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application relates to the technical field of sodium ion batteries, and discloses a ball-milling calcination preparation method of a carbon nanotube and glucose composite-coated sodium iron pyrophosphate sulfate positive electrode material. In view of the limitations of narrow calcination window of a single sulfate and low voltage of a pyrophosphate, the application realizes uniform mixing of sulfate and pyrophosphate through high-energy ball milling, introduces a carbon nanotube and glucose double carbon source, and in-situ constructs a Na2Fe2P2O7SO4 / CNT-Glu composite positive electrode material through calcination. The material utilizes the high electronegativity of sulfate to improve the working voltage, and utilizes the stable network of pyrophosphate to guarantee the structural stability; the double carbon source forms a three-dimensional conductive framework, and significantly improves the electron transmission kinetics. Experiments show that the initial specific capacity of the material is 114.09 mAh / g at 0.05 C, the reversible capacity is 95.37 mAh / g at 0.2 C, the retention rate is 94.43% after 100 cycles, the reversible capacity is 83.40 mAh / g at 2 C, and the retention rate is 91.56% after 400 cycles, so that the material has high voltage, excellent rate and super-long cycle performance, and provides a feasible way for the development of a low-cost and high-safety sodium ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a ball milling and calcination method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material, belonging to the field of sodium-ion battery technology. Background Technology

[0002] Driven by profound changes in the global energy structure and the goal of carbon neutrality, developing electrochemical energy storage technologies that are economically efficient, highly safe, and environmentally adaptable has become a common focus for industry and academia. Sodium-ion batteries, due to the high abundance and wide distribution of sodium in the Earth's crust, significantly lower raw material costs compared to lithium-ion systems, and the ability to utilize existing lithium-ion battery production line equipment, are rapidly emerging as a key technology for large-scale energy storage, short-distance transportation, and microgrids. Polyanionic cathode materials, with their open three-dimensional framework structure, stable anionic group-induced effects, and excellent stability and cycle durability, have become the mainstream choice for sodium-ion battery cathode research and development.

[0003] While sulfate-based polyanionic compounds (typically alluaudite phase Na2Fe2(SO4)3) possess a high potential plateau of approximately 3.8 V and cost advantages in raw materials, they face bottlenecks such as low intrinsic electron mobility and a stringent sintering process window—temperatures exceeding 400 °C trigger sulfate decomposition and ferrous ion oxidation, resulting in lattice defects and a sharp decline in capacity. Pyrophosphate materials (such as Na2FeP2O7), although exhibiting excellent thermal stability and compatibility with high-temperature carbon coating processes, suffer from low redox potentials and mass energy densities, making them unsuitable for high-power applications.

[0004] Existing carbon coating strategies mostly rely on a single carbon source, such as mechanical mixing of carbon from glucose pyrolysis or conductive carbon black. While in-situ pyrolysis of glucose results in uniform dispersion, it leads to low residual carbon content and poor graphitization, making it difficult to form a highly efficient conductive network. Conductive carbon black, although exhibiting fast electron transport, is highly hydrophobic, prone to agglomeration, and has poor interfacial contact with active materials, while also adding an extra electrode preparation step. Although carbon nanotubes possess excellent one-dimensional conductivity, direct ball milling easily leads to entanglement and agglomeration, making uniform dispersion on the surface of polyanionic particles difficult. None of the aforementioned single carbon coating routes can simultaneously meet the triple requirements of "high conductivity, strong interfaciality, and low cost." There is an urgent need to develop a composite carbon coating strategy that synergistically leverages the advantages of various carbon sources to achieve a comprehensive leap in the electrochemical performance of sodium iron pyrophosphate sulfate materials. Summary of the Invention

[0005] The purpose of this invention is to provide a ball milling and calcination method for preparing a Na2Fe2P2O7SO4 / CNT-Glu composite cathode material coated with carbon nanotubes and glucose. A synergistic process based on a composite polyanionic framework and a composite carbon coating strategy is proposed to construct a Na2Fe2P2O7SO4 / CNT-Glu composite cathode material that exhibits both a high voltage platform and high structural stability. This method achieves SO42-coated sodium pyrophosphate at room temperature under mechanochemical conditions. 2- P2O7 4- with Fe 2+ The mixture is uniformly mixed and simultaneously introduced as a dual carbon source of carbon nanotubes and glucose. In the subsequent calcination stage, mechanical force-induced lattice pre-arrangement is used to form a pure phase composite polyanionic framework. At the same time, in-situ pyrolysis of glucose and interweaving of carbon nanotubes construct a three-dimensional composite conductive network, achieving efficient synergy between electron transport and ion diffusion.

[0006] The objective of this invention can be achieved through the following technical solutions: A method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate sulfate cathode material by ball milling and calcination includes the following steps: (1) Sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, diammonium hydrogen phosphate, solvent, antioxidant and / or carbon source are added to a ball mill jar in molar ratio and processed at a uniform speed to obtain a mixed precursor slurry; the precursor slurry is dried and ground in a mortar to obtain a uniform mixed precursor powder; (2) The mixed precursor powder is calcined in a tube furnace, heated to 400~600 ℃ for 8~12 h in an inert atmosphere, and then cooled to room temperature after sintering to obtain a sodium iron phosphate sulfate composite cathode material.

[0007] Furthermore, in step (1), the molar ratio of sodium carbonate to ammonium sulfate is 0.75~1.25:1, the molar ratio of ferrous oxalate dihydrate to ammonium sulfate is 0.5~2:1, and the molar ratio of diammonium hydrogen phosphate to ammonium sulfate is 1~3:1. The resulting cathode material has the chemical formula Na. a Fe b (P2O7) c SO4, where 1.5≤a≤2.5, 0.5≤b≤2, and 0.5≤c≤1.5.

[0008] Furthermore, in step (1), the solvent is acetone, ethanol or water, and the mass ratio of the solvent to the mixed precursor powder is 0.75~1.5:1.

[0009] Furthermore, in step (1), the antioxidant is citric acid or ascorbic acid, and the citric acid reacts with Fe... 2+ The molar ratio is 1:10.

[0010] Furthermore, in step (1), the carbon source accounts for 0-10% of the mass of sodium iron pyrophosphate sulfate, and the carbon source is sucrose, maltose, glucose, carbon nanotubes, acetylene black or Ketjen black.

[0011] Furthermore, in step (1), the rotation speed of the ball mill is 400~500 rpm, and the ball milling time is 8~12h.

[0012] Furthermore, in step (1), the drying method is vacuum drying, spray drying or flash drying, and the drying temperature is 100 ℃~200 ℃.

[0013] Furthermore, in step (2), the inert gas is at least one of Ar or N2, and the calcination heating rate is 3 °C / min. Beneficial effects

[0014] This invention discloses a ball milling and calcination method for preparing a sodium iron pyrophosphate (Na2Fe2P2O7SO4) composite cathode material coated with carbon nanotubes and glucose. Based on a mechanochemical-assisted solid-state synthesis strategy, this method achieves, for the first time, the simultaneous introduction and synergistic coating of carbon nanotubes and glucose as dual carbon sources in a sulfuric acid pyrophosphate system, successfully constructing a Na2Fe2P2O7SO4 / CNT-Glu composite cathode material. This composite polyanionic framework cleverly combines the high voltage characteristics of sulfate with the high thermodynamic stability of pyrophosphate: the sulfate ion effectively enhances the Fe content through its strong electronegativity induction effect. 3+ / Fe 2+ The redox potential is controlled by pyrophosphate, which inhibits lattice oxygen loss through a stable covalent bond network. Together, they overcome the inherent bottlenecks of narrow calcination windows (<400 °C) and the limitations of single-sulfate pyrophosphate. At the process level, high-energy ball milling achieves uniform ionic dispersion of multiple components. Simultaneously, glucose undergoes in-situ pyrolysis during calcination to form highly active amorphous carbon, which interweaves with added carbon nanotubes to form a three-dimensional hybrid conductive framework with a "line-point" connection. Carbon nanotubes act as the main long-range electron transport pathway, while amorphous carbon serves as an interfacial affinity bridge. Together, they significantly reduce electrode polarization resistance and improve the wettability of the active material and the electrolyte. Experimental data show that the Na2Fe2P2O7SO4-CNT-2-Glu-3 composite material prepared using the method of this invention achieves an initial discharge specific capacity of 114.09 mAh / g at 0.05 C, a reversible discharge specific capacity of 95.37 mAh / g at 0.2 C, and a reversible discharge specific capacity of 83.40 mAh / g at 2 C, with a capacity retention rate of 91.56% after 400 cycles. Its overall performance is significantly superior to that of a single carbon source coating system. This invention provides a practical and feasible technical route for the large-scale preparation of sodium-ion battery cathode materials that combine the advantages of high voltage, long lifespan, and low cost. Attached Figure Description

[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below.

[0016] Figure 1 This is a SEM image of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material in Example 1.

[0017] Figure 2 This is the XRD pattern of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material in Example 1.

[0018] Figure 3 The first constant current charge-discharge performance at 0.05 C of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material in Example 1 is shown.

[0019] Figure 4 The first constant current charge-discharge performance at 0.05 C of the Na2Fe2P2O7SO4-CNT-2-Glu-2 cathode material in Example 2 is shown.

[0020] Figure 5 The first constant current charge-discharge performance at 0.05 C of the Na2Fe2P2O7SO4-CNT-2-Glu-4 cathode material in Example 3 is shown.

[0021] Figure 6 This refers to the initial constant current charge-discharge performance of the Na2Fe2P2O7SO4-0 cathode material at 0.05 C in Example 4.

[0022] Figure 7 The first constant current charge-discharge performance at 0.05 C of the Na2Fe2P2O7SO4-CNT-2 cathode material in Example 5 is shown.

[0023] Figure 8 The first constant current charge-discharge performance at 0.05 C of the Na2Fe2P2O7SO4-CNT-5 cathode material in Example 6 is shown.

[0024] Figure 9 The first constant current charge-discharge performance at 0.05 C of the Na2Fe2P2O7SO4-CNT-10 cathode material in Example 7 is shown.

[0025] Figure 10 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-CNT-2-Glu-3 in Example 1.

[0026] Figure 11 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-CNT-2-Glu-2 in Example 2.

[0027] Figure 12 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-CNT-2-Glu-4 in Example 3.

[0028] Figure 13 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-0 in Example 4.

[0029] Figure 14 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-CNT-2 in Example 5.

[0030] Figure 15 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-CNT-5 in Example 6.

[0031] Figure 16 This refers to the 0.2 C cycle capacity performance of Na2Fe2P2O7SO4-CNT-10 in Example 7.

[0032] Figure 17 This refers to the 2C cycle capacity performance of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material in Example 1.

[0033] Figure 18 This is a rate performance test of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material in Example 1. Detailed Implementation

[0034] The present invention will be further described in detail below with reference to specific embodiments.

[0035] In the following embodiments or comparative examples: (1) Sodium-ion battery assembly: At room temperature, CR2032 button batteries were assembled and electrochemical performance was tested. First, the active material, conductive agent and binder prepared in the example or comparative example were weighed in a mass ratio of 70:20:10 and ground in N-methylpyrrolidone for 30-40 min to obtain a black uniform slurry. The slurry was evenly coated on a flat aluminum foil with a scraper and dried in a vacuum oven at 100 °C for 12 h to remove N-methylpyrrolidone. Finally, the aluminum foil coated with the sample was cut into positive electrode sheets with a diameter of 1.1 cm using a cutting machine. (2) Electrochemical performance test: Sodium sheet was used as the negative electrode, glass fiber as the separator, and 1 M NaClO4 (EC:PC=1:1, containing 5% FEC) as the electrolyte. Charge and discharge tests were conducted using the Xinwei Battery Test System. The test voltage range was 1.7~4.5 V and 2.0~4.5 V, the test temperature was 30 ℃, and the test current density was 0.05~2.0 C (1 C=100 mA / g). Example 1

[0036] Preparation of Na2Fe2P2O7SO4-CNT-2-Glu-3 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+ A suitable amount of citric acid, 2 wt% carbon nanotubes, and 3 wt% glucose were added at a molar ratio of 10:1. A suitable amount of acetone was added at a solvent-to-mixed precursor powder mass ratio of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black, viscous precursor material. The precursor material was vacuum-dried at 100℃ for 12 h in a vacuum oven, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600℃ for 10 h in an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain a Na2Fe2P2O7SO4-CNT-2-Glu-3 composite cathode material in the crucible.

[0037] Figure 1 The image shows a scanning electron microscope (SEM) image of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material prepared in Example 1. As can be seen from the image, the material exhibits an irregular granular morphology, with a layered carbonaceous film uniformly coated on the particle surface. Carbon nanotubes are interwoven and embedded in the particles and on the surface, effectively bridging adjacent active particles and forming a continuous three-dimensional conductive pathway. Abundant mesoporous structures are visible between the particles, which facilitates electrolyte penetration and Na+ exchange. + Fast transmission.

[0038] Figure 2 The X-ray diffraction pattern of the Na2Fe2P2O7SO4-CNT-2-Glu-3 cathode material prepared in Example 1 shows sharp peaks, narrow full width at half maximum (FWHM), and excellent signal-to-noise ratio, indicating high crystallinity of the prepared material. No diffraction peaks of residual raw material phases were detected in the spectrum, nor were common impurity phases such as Na6Fe(SO4)4 present, indicating that SO42-... 2- With P2O7 4- It has completely entered the crystal lattice to form the target complex phase.

[0039] like Figure 3As shown, the sodium-ion battery assembled in Example 1, with a current density of 0.05 C and a test voltage range of 1.7~4.5 V, exhibits an initial discharge specific capacity of 114.09 mAh / g, demonstrating excellent reversible sodium-ion insertion / extraction characteristics.

[0040] The performance of the assembled battery at 0.2 C is as follows: Figure 10 As shown, Example 1 exhibits a reversible discharge specific capacity of 95.37 mAh / g, with a capacity retention of 94.43% after 100 cycles. According to... Figure 17 As a result, the sodium-ion battery assembled in Example 1 exhibited a discharge specific capacity of 83.40 mAh / g at a 2 C rate. After 400 cycles, it still maintained 91.56% of its capacity. This fully demonstrates that the successful preparation of this composite material significantly enhances the electrochemical cycling stability of the polyanionic material.

[0041] like Figure 18 As shown, the material exhibits excellent discharge specific capacity at different current densities, indicating that the composite framework of sulfate and pyrophosphate was constructed by ball milling, and the simultaneous introduction of carbon nanotubes and glucose as dual carbon sources effectively constructed a three-dimensional hybrid conductive network with the synergistic effect of long-range conductivity of carbon nanotubes and affinity of amorphous carbon interfaces, thereby significantly improving its capacity utilization and reaction kinetics performance under high-rate conditions. Example 2

[0042] Preparation of Na2Fe2P2O7SO4-CNT-2-Glu-2 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+ A suitable amount of citric acid, 2 wt% carbon nanotubes, and 2 wt% glucose were added at a molar ratio of 10:1. A suitable amount of acetone was added at a solvent-to-mixed precursor powder mass ratio of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black, viscous precursor material. The precursor material was vacuum-dried at 100℃ for 12 h in a vacuum oven, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600℃ for 10 h in an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain a Na2Fe2P2O7SO4-CNT-2-Glu-2 composite cathode material in the crucible.

[0043] The electrochemical performance of the assembled battery is as follows: Figure 4 and Figure 11As shown, the test voltage range is 1.7~4.5 V. The reversible discharge specific capacity of Example 2 at a rate of 0.2 C is 71.61 mAh / g, and the capacity retention rate is 91.89% after 100 cycles. Example 3

[0044] Preparation of Na2Fe2P2O7SO4-CNT-2-Glu-4 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+ A suitable amount of citric acid, 2 wt% carbon nanotubes, and 4 wt% glucose were added at a molar ratio of 10:1. A suitable amount of acetone was added at a solvent-to-mixed precursor powder mass ratio of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black, viscous precursor material. The precursor material was vacuum-dried at 100℃ for 12 h in a vacuum oven, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600℃ for 10 h in an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain a Na2Fe2P2O7SO4-CNT-2-Glu-4 composite cathode material in the crucible.

[0045] The electrochemical performance of the assembled battery is as follows: Figure 5 and Figure 12 As shown, the test voltage range is 1.7~4.5 V. The reversible discharge specific capacity of Example 3 at a rate of 0.2 C is 88.91 mAh / g, and the capacity retention rate is 99.80% after 100 cycles. Example 4

[0046] Preparation of Na2Fe2P2O7SO4-0 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+ A suitable amount of lemon was added at a molar ratio of 10:1, and a suitable amount of acetone was added at a mass ratio of solvent to mixed precursor powder of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black viscous precursor material. The precursor material was vacuum-dried in a vacuum oven at 100 °C for 12 h, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600 °C for 10 h under an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain the Na2Fe2P2O7SO4-0 composite cathode material in the crucible.

[0047] The electrochemical performance of the assembled battery is as follows: Figure 6 and Figure 13 As shown, the test voltage range is 1.7~4.5 V. In Example 4, the reversible discharge specific capacity at a rate of 0.2 C is 51.56 mAh / g, and the capacity retention rate is 59.93% after 100 cycles. Example 5

[0048] Preparation of Na2Fe2P2O7SO4-CNT-2 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+ Citric acid and 2 wt% carbon nanotubes were added at a molar ratio of 10:1, and acetone was added at a solvent-to-precursor powder mass ratio of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black viscous precursor material. The precursor material was vacuum-dried at 100 °C for 12 h in a vacuum oven, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600 °C for 10 h in an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain Na2Fe2P2O7SO4-CNT-2 composite cathode material in the crucible.

[0049] The electrochemical performance of the assembled battery is as follows: Figure 7 and Figure 14 As shown, the test voltage range is 1.7~4.5 V. In Example 5, the reversible discharge specific capacity at a rate of 0.2 C is 64.98 mAh / g, and the capacity retention rate is 78.99% after 100 cycles. Example 6

[0050] Preparation of Na2Fe2P2O7SO4-CNT-5 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+Citric acid and 5 wt% carbon nanotubes were added at a molar ratio of 10:1, and acetone was added at a solvent-to-precursor powder mass ratio of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black viscous precursor material. The precursor material was vacuum-dried at 100 °C for 12 h in a vacuum oven, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600 °C for 10 h in an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain Na2Fe2P2O7SO4-CNT-5 composite cathode material in the crucible.

[0051] The electrochemical performance of the assembled battery is as follows: Figure 8 and Figure 15 As shown, the test voltage range is 1.7~4.5 V. In Example 6, the reversible discharge specific capacity at a rate of 0.2 C is 70.14 mAh / g, and the capacity retention rate is 99.54% after 100 cycles. Example 7

[0052] Preparation of Na2Fe2P2O7SO4-CNT-10 material: Weigh out sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, and diammonium hydrogen phosphate in a molar ratio of 1:2:1:2 and add them to a ball mill jar. During the process, add citric acid and Fe... 2+ Citric acid and 10 wt% carbon nanotubes were added at a molar ratio of 10:1, and acetone was added at a solvent-to-precursor powder mass ratio of 1:1. The mixture was ball-milled at 500 rpm for 12 h to obtain a black viscous precursor material. The precursor material was vacuum-dried at 100 °C for 12 h in a vacuum oven, cooled to room temperature, and ground to obtain precursor powder. The mixed precursor powder was placed in a crucible and calcined in a tube furnace at 600 °C for 10 h in an Ar sintering atmosphere. After calcination, it was cooled to room temperature to obtain Na2Fe2P2O7SO4-CNT-10 composite cathode material in the crucible.

[0053] The electrochemical performance of the assembled battery is as follows: Figure 9 and Figure 16 As shown, the test voltage range is 1.7~4.5 V. The reversible discharge specific capacity of Example 7 at a rate of 0.2 C is 39.90 mAh / g, and the capacity retention rate is 86.74% after 100 cycles. Comparative Example 1

[0054] Preparation of Na 2+2x Fe 2-x (SO4)3-1 Materials: Sodium sulfate and ferrous sulfate heptahydrate in a 1:1 molar ratio were weighed and added to 25 ml of deionized water, with appropriate amounts of ascorbic acid and glucose added during the process. The resulting mixed solution was slowly added dropwise to 100 ml of ethanol solution to obtain a gray-green precipitate. The precipitate was washed with ethanol and filtered. The precipitate was dried in a vacuum oven at 60 °C for 12 h and then ground to obtain precursor powder. The mixed precursor powder was placed in a ceramic boat and calcined in a tube furnace at 350 °C for 2 h under an Ar gas atmosphere. After calcination, the mixture was cooled to room temperature to obtain Na in a crucible. 2+2x Fe 2-x (SO4)3-1 cathode material.

[0055] The electrochemical performance of the battery assembled in Comparative Example 1 was 22.5 mAh / g at 0.1 C discharge capacity and the test voltage range was 2.0~4.5 V. Comparative Example 2

[0056] Preparation of Na 2+2x Fe 2-x (SO4)3-2 Materials: Sodium sulfate and ferrous sulfate heptahydrate in a molar ratio of 1:2 were weighed and added to 25 ml of deionized water, with appropriate amounts of ascorbic acid and glucose added during the process. The resulting mixed solution was slowly added dropwise to 100 ml of ethanol solution to obtain a gray-green precipitate. The precipitate was washed with ethanol and filtered. The precipitate was dried in a vacuum oven at 60 °C for 12 h and then ground to obtain precursor powder. The mixed precursor powder was placed in a ceramic boat and calcined in a tube furnace at 350 °C for 2 h under an Ar gas atmosphere. After calcination, the mixture was cooled to room temperature to obtain Na in a crucible. 2+2x Fe 2-x (SO4)3-2 cathode material.

[0057] The electrochemical performance of the battery assembled in Comparative Example 2 was as follows: discharge capacity of 21.0 mAh / g at 0.1 C, and test voltage range of 2.0~4.5 V.

[0058] Experimental data show that the Na2Fe2P2O7SO4 / CNT-Glu composite cathode material prepared in this invention possesses the triple advantages of high specific capacity, excellent rate performance, and ultra-long cycle life. The strong inductive effect of sulfate and the structural anchoring effect of pyrophosphate in the composite polyanionic framework complement each other, ensuring lattice integrity while increasing the operating voltage. Furthermore, the bifunctional network of "long-range conductivity + interfacial affinity" constructed from carbon nanotubes and glucose pyrolysis carbon effectively reduces charge transfer impedance and promotes Na... +Diffusion kinetics. This preparation process is simple, uses inexpensive raw materials, and has a suitable calcination temperature, making it feasible for industrial scale-up. It opens up a new avenue for the efficient and green manufacturing of polyanionic sodium cathode materials.

[0059] In summary, the invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered to be within the protection scope of this invention.

Claims

1. A method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate sulfate cathode material by ball milling and calcination, characterized in that, The novel carbon-coated sodium iron pyrophosphate composite polyanionic cathode material is prepared using the following steps: (1) Sodium carbonate, ferrous oxalate dihydrate, ammonium sulfate, diammonium hydrogen phosphate, solvent, antioxidant and / or carbon source are added to a ball mill jar in molar ratio and processed at a constant speed to obtain a mixed precursor slurry; the precursor slurry is dried and ground in a mortar to obtain a mixed precursor powder; (2) The mixed precursor powder is calcined in a tube furnace, heated to 400~600℃ for 8~12 h in an inert atmosphere, and then cooled to room temperature after sintering to obtain a sodium iron pyrophosphate sulfuric acid composite cathode material.

2. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The sodium-ion battery is prepared using the following steps: At room temperature, CR2032 button cells were assembled and their electrochemical performance was tested. First, the active material, conductive agent, and binder prepared in the examples or comparative examples were weighed at a mass ratio of 7:2:1 and ground in N-methylpyrrolidone for 30-40 min to obtain a black uniform slurry. The slurry was then uniformly coated onto a flat aluminum foil with a scraper and dried in a vacuum oven at 100 °C for 12 h to remove N-methylpyrrolidone. Finally, the aluminum foil coated with the sample was cut into positive electrode sheets with a diameter of 1.1 cm using a cutting machine. Sodium sheet was used as the negative electrode, glass fiber as the separator, and 1 M NaClO4 (EC:PC=1:1, containing 5% FEC) as the electrolyte. Charge-discharge tests were conducted using the Xinwei Battery Testing System. The test voltage range was 1.7-4.5 V and 2.0-4.5 V, the test temperature was 30 °C, and the test current density was 0.05-2.0 C (1 C=100 mA / g).

3. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The molar ratio of sodium carbonate to ammonium sulfate is 0.75~1.25:1, the molar ratio of ferrous oxalate dihydrate to ammonium sulfate is 0.5~2:1, and the molar ratio of diammonium hydrogen phosphate to ammonium sulfate is 1~3:

1. The resulting cathode material has the chemical formula Na. a Fe b (P2O7) c SO4, where 1.5≤a≤2.5, 0.5≤b≤2, and 0.5≤c≤1.

5.

4. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The solvent is acetone, ethanol, or water, and the mass ratio of the solvent to the mixed precursor powder is 0.75~1.5:

1.

5. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The antioxidant is citric acid or ascorbic acid, wherein the citric acid reacts with Fe... 2+ The molar ratio is 1:

10.

6. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The carbon source accounts for 0-10% of the mass of sodium iron pyrophosphate sulfate, and the carbon source is sucrose, maltose, glucose, carbon nanotubes, acetylene black, or Ketjen black.

7. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The ball milling speed is 400~500 rpm, and the ball milling time is 8~12 h.

8. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that, The drying method is vacuum drying, spray drying or flash drying, and the drying temperature is 100 ℃~200 ℃.

9. The method for preparing a carbon nanotube and glucose composite coated sodium iron pyrophosphate cathode material by ball milling and calcination according to claim 1, characterized in that... The inert gas is at least one of Ar or N2, and the calcination heating rate is 3°C / min.